Phosphatase and Tensin Homologue: Novel Regulation by Developmental Signaling. (3rd August 2015) - Jerde, Travis J.
Abstract : Phosphatase and tensin homologue (PTEN) is a critical cell endogenous inhibitor of phosphoinositide signaling in mammalian cells. PTEN dephosphorylates phosphoinositide trisphosphate (PIP3 ), and by so doing PTEN has the function of negative regulation of Akt, thereby inhibiting this key intracellular signal transduction pathway. In numerous cell types, PTEN loss-of-function mutations result in unopposed Akt signaling, producing numerous effects on cells. Numerous reports exist regarding mutations in PTEN leading to unregulated Akt and human disease, most notably cancer. However, less is commonly known about nonmutational regulation of PTEN. This review focuses on an emerging literature on the regulation of PTEN at the transcriptional, posttranscriptional, translational, and posttranslational levels. Specifically, a focus is placed on the role developmental signaling pathways play in PTEN regulation; this includes insulin-like growth factor, NOTCH, transforming growth factor, bone morphogenetic protein, wnt, and hedgehog signaling. The regulation of PTEN by developmental mediators affects critical biological processes including neuronal and organ development, stem cell maintenance, cell cycle regulation, inflammation, response to hypoxia, repair and recovery, and cell death and survival. Perturbations of PTEN regulation consequently lead to human diseases such as cancer, chronic inflammatory syndromes, developmental abnormalities, diabetes, and neurodegeneration.